The Role of Lean Human Resources in Promoting Organizational Citizenship Behavior: A Systematic Literature Review - Haryanto, Tri; Ahman, Eeng; Askolani, Askolani (Green Publisher Indonesia, 2025)
In addressing the complexity of modern organizational environments, the implementation of Lean Human Resources (Lean HR) has emerged as a strategic approach to enhancing efficiency and employee empowerment. This study aims to examine the relationship between Lean HR and Organizational Citizenship Behavior (OCB), as well as to explore the role of organizational culture as a moderating variable in that relationship. The method employed is a Systematic Literature Review (SLR) based on the PRISMA protocol, analyzing 40 empirical articles from the Scopus database published between 2024 and 2025. The analysis was conducted using VOSviewer and Biblioshiny to support bibliometric mapping and thematic visualization. The findings indicate that Lean HR principles—such as process efficiency, empowerment, continuous training, and transparency—have a positive relationship with OCB dimensions, including altruism, civic virtue, and conscientiousness. Moreover, an organizational culture that fosters collaboration and learning plays a crucial role in strengthening the influence of Lean HR on OCB. Bibliometric visualizations identified “employee” and “organization” as central nodes in the relevant literature. In conclusion, the integration of Lean HR with an adaptive organizational culture significantly fosters the development of OCB. This study offers both theoretical and practical contributions to the advancement of strategic human resource management in navigating contemporary organizational dynamics.